Systematic Literature Review: Arsitektur, Mekanisme Teknis, dan Metrik Kinerja pada Penerapan Blockchain di Sektor Kesehatan - Shesyl Yulia Noor Diwani; Cindy Jumaida; Daud Sihar Surung Putra Anugerah Daeli; Natalis Pardamean Situmorang; Anelka Winata Perangin Angin; Yohana Angeliana Sianturi; Muhammad Abdillah Helmi Rasyid; Sudarto Sudarto (Jurnal Teknologi Terpadu, 2026)
The widespread adoption of digital technology in the healthcare sector has driven the need for transparent, secure, and reliable data management systems, especially those for sensitive patient data and the drug supply chain. Blockchain technology is seen as a potential solution due to its decentralised, immutable, and transparent characteristics. This study aims to identify and analyse the use of blockchain technology in the healthcare sector, focusing on patient data transparency and the efficiency of pharmaceutical supply chains. Using the PRISMA-guided Systematic Literature Review (SLR) method, this research examines 18 Scopus-indexed articles (Q1–Q3) published between 2020 and 2025. The analysis shows that the Hyperledger Fabric platform and Permissioned Blockchain architecture dominate due to their efficiency and suitability for consortium-based systems. The main supporting technologies applied include smart contracts, IPFS-based off-chain storage, and consensus mechanisms such as PoA and PBFT. Empirically, the implementation of blockchain has been proven to improve transaction efficiency, supply chain traceability, and the integrity and security of patient data. However, technical challenges such as scalability, interoperability, and compliance with global privacy regulations remain obstacles. This study contributes by mapping healthcare blockchain architectures and technological trends, and by offering future research directions for performance optimisation and system adoption.